Poor Mental Health as Cause and/or Consequence of Restrictive Housing - Wooldredge, John (Criminal justice and behavior, 2025)
Whether poor mental health increases an incarcerated person’s exposure to disciplinary or administrative segregation, and, in turn, whether segregation contributes to poorer health have been examined separately in the empirical literature, with studies of the former limited to between-person analyses. We conducted within-person analyses of changes to both mental health and the odds of segregation to determine whether these effects are bidirectional within the same sample. Between-person analyses of mental health effects on segregation were also performed for comparison to prior studies. Admissions to all Ohio prisons within a 10-year window (N = 224,288) were examined. Within-person analyses revealed lower odds of placement in administrative segregation for individuals with declining mental health during their sentence and no significant segregation effects on subsequent mental health. Between-person analyses indicated higher odds of placement in disciplinary segregation within the first year of confinement for persons with poorer mental health at prison intake.